Practical Aspects of Botulinum Toxin-A Treatment in Patients With Overactive Bladder Syndrome - Chun-Hou Liao; Hann-Chorng Kuo (International Neurourology Journal, 2015)
Intravesical onabotulinumtoxinA (BoNT-A) injection is an effective treatment for overactive bladder syndrome (OAB) that is refractory to antimuscarinics. An injectable dose of 100 U has been suggested to achieve the optimal balance of benefit and safety in patients with OAB. BoNT-A (total volume of 10 mL) was administered as evenly distributed intradetrusor injections (5 U) across 20 sites approximately 1 cm apart (0.5 mL per site) using a flexible or rigid cystoscope. Treatment with BoNT-A was generally well tolerated by most patients, and most treatment-related adverse events were localized to the urinary tract. The prevalence of OAB increases with age, and elderly patients are more vulnerable to complications. The short-term efficacy of intravesical BoNT-A injection for refractory OAB with no treatment-related complications in the elderly population has been documented. Frail elderly patients can experience the same treatment results, such as significantly improved urgent urinary incontinence and quality of life, as young and nonfrail elderly patients with 100-U BoNT-A injections. However, increased risk of larger postvoid residual (PVR) urine and lower long-term success rates were noted in frail elderly patients; around 11% had acute urinary retention, while 60% had PVR urine volume >150 mL after treatment. In addition, intravesical injection of BoNT-A effectively decreased urgency symptoms in elderly patients with OAB and central nervous system lesions. The adverse effects were acceptable, while the long-term effects were comparable to those in patients with OAB without central nervous system lesions. Nonetheless, the possibility of longstanding urinary retention and chronic catheterization in this vulnerable population requires careful evaluation before treatment with intravesical BoNT-A. In conclusion, the current findings indicate that intravesical BoNT-A is an effective and safe treatment for OAB in elderly patients.